Keefektifan Termisida Nabati Berbahan Aktif Rotenone terhadap Mortalitas dan Perubahan Perilaku Hama Rayap Tanah (Coptotermes curvignathus) - Danie Indra Yama (JURNAL CITRA WIDYA EDUKASI, 2018)
The losses of palm oil plantation in Indonesia caused by soil termites (Coptotermes curvignathus) are around Rp 224 billion – Rp 238 billion per year. How to overcome it with botanical termicide tubal root (Derris elliptica) that has the content of toxin rotenone. The purpose of this research is to know the effectivity of tubal root extract as botanical termicide to control termites, the correct concentration and behavior termites to on its application. The research was conducted at Biological Laboratory of Politeknik Kelapa Sawit Citra Widya Edukasi, Bekasi on February 2017 used Completely Randomized Design with tubal root extract treatment : A1: 15 gr /L, A2: 30 gr /L, A3: 45 gr /L, A4: 60 gr /L by three replication and consisted of 10 Coptotermes curvignathus per unit. Tubal root extract is made by soaking it into water then saturated 24 hours and the water is taken. Its application is sprayed at 30 cm distance and height as much as 5 sprays. Data were analized by analysis of variance with α = 5%, if there a significant treatment effect then tested continued using LSD (Least Significance Different). The parameters used are the beginning of termite mortality, mortality, behavior change. The result showed that tubal root extract was effective in controlling termites with 83.33% mortality with soil termite mortality time at 4.85 minute. Tuba root extract application effective at 60 g/l. Tubal root extract affect the decreasing activity and morphological changes from pale yellow to black.